2018
DOI: 10.4103/ccd.ccd_15_18
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of shear bond strength of orthodontic brackets bonded with different adhesives

Abstract: Background:There is necessary of dry operating field for bonding of orthodontic brackets. The presence of moisture can alter the bond strength. Hence, the aim of the present study was to evaluate the shear bond strength of orthodontic brackets with different adhesives.Materials and Methods:In this in vitro study, a total of 100 orthodontically extracted premolars with sound crown structure were divided into 4 equal groups of different primers. Bonding on the buccal surface of all teeth was done after acid etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…35,36 The applied force at fracture time was recorded in Newton then it was converted into megapascals (MPa) by dividing the debonding force by the surface area of the bracket. 37,38 The amount of the residual adhesive remained on the enamel surface was quantified by the adhesive remnant index (ARI). 39 After debonding, the teeth were examined under 10 × magnifications microscope.…”
Section: Shear Bond Strength Measurementmentioning
confidence: 99%
“…35,36 The applied force at fracture time was recorded in Newton then it was converted into megapascals (MPa) by dividing the debonding force by the surface area of the bracket. 37,38 The amount of the residual adhesive remained on the enamel surface was quantified by the adhesive remnant index (ARI). 39 After debonding, the teeth were examined under 10 × magnifications microscope.…”
Section: Shear Bond Strength Measurementmentioning
confidence: 99%
“…The demand for usage of various adhesives by dental practitioners has led to the emergence of newer universal self-etch adhesive systems (USEASs). [ 7 8 ] It has a less invasive pH (1.5<pH<3) and bonding employed with acidic functional monomers glycerol dimethacrylate dihydrogen phosphate (GPDM) and 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP), available in both self-etch and total-etch modes. When employed in a self-etch mode, USEASs may remarkably simplify the bonding procedure by decreasing the steps in bonding, number of eroded enamel rods, and eliminating the necessity for total acid etching.…”
Section: Introductionmentioning
confidence: 99%
“…ARI is one of the most commonly used parameters for evaluating the quality of adhesion between the adhesive and the tooth and also between the adhesive and the bracket. 34 It is desirable that after debonding some adhesive is left on the tooth surface, thereby minimizing the damage of enamel surface during bracket removal procedures. The present study results showed that there were no significant differences concerning ARI at all the concentrations of chitosan NPs and TiO 2 NPs.…”
Section: Discussionmentioning
confidence: 99%